Biological yield of winter triticale grain with various option for pre-sowing fertilization and top dressing in the Northern Steppe of Ukraine - Belashov О.; Rozhkov, A. (Scientific Progress & Innovations, 2022)
The purpose of the research was to determine the influence of various options for pre-sowing application of complex fertilizers in interaction with foliar fertilization on the biological yield of the grain of the main and side stems of triticale winter variety Shalanda. The research was carried out during 2018–2020 in the field of the private agricultural enterprise «Shevchenko» of the Velykoburlutsk district of the Kharkiv region according to accepted methods. The two-factor experiment was carried out by the method of split plots in four repetitions. The experiments studied the effectiveness of three options for pre-sowing fertilization with seven options of foliar fertilization (21 options). The area of the sowing plot was 150 m2, the accounting plot was 100 m2. Agricultural technology in experiments was generally accepted for the territory of research, with the exception of the elements put to study. A different temperature regime and significant differences in the amount of precipita-tion and its distribution during the springsummer vegetation of winter triticale made significant corrections in the course of plant growth processes, which significantly affected the indicators of biological grain yield. At the same time, it made it possible to more fully determine the impact of the studied options on the level of this indicator. The highest biological yield of the main and side system of winter triticale stems in the conducted studies – 5.21 and 1.68 t/ha respectively, was formed in the variant of presowing application of ammophos (N12P52), root top dressing with am-monium nitrate (N50) during the 22 microphase according to the international scale of the BBCH, followed by two foliar feedings during the 31 and 39 microphases with a mixture of urea (10 kg/ha), magnesium sulfate (1.5 kg/ha) and complex watersoluble fertilizer Ferkrystal Summum (1.5 kg/ha). Late foliar fertilizing with a mixture of these fertilizers during the 73 microphase did not provide significant increase in the biological yield of both stem systems of winter triticale in any year. The high efficiency of the complex watersoluble Ferkrystal Su mmum fertilizer has been proven. Its addition to the working mixture of urea and magnesium sulfate during foliar fertilization in microphases 31 and 39 ensured a significant increase in the biological yield of both the main and side system of winter triticale stems. In particular, on average over three years of research, the addition of this fertilizer to the biological yield of grain from the main and side stems of winter triticale by 0.14 and 0.09 t/ha respectively (LSD05 – 0.10 and 0.05 t/ha respectively).